Pengaruh Model Pembelajaran Problem Solving Terhadap Keaktifan Belajar Peserta Didik Dalam Pembelajaran Pendidikan Agama Kristen dan Budi Pekerti di Kelas X SMA Negeri 1 Sipoholon Tahun - Juan Andreas Manurung; Hasudungan Simatupang; Tahadodo Waruwu; Eben H. Telaumbanua; Baginda Sitompul (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
The purpose of this study was to determine the effect of the Problem Solving learning model on student learning activity in Christian Religious Education and Character Education in class X of SMA Negeri 1 Sipoholon in the 2024/2025 Academic Year. The method used in this study uses a quantitative research method. The population is all Protestant Christian students in class X of SMA Negeri 1 Sipoholon in the 2024/2025 Academic Year, totaling 271 people and 41 people were determined as research respondents, namely 15% of the population. Data were collected using a positive closed questionnaire of 50 items. The results of the data analysis show that there is an influence of the Problem Solving learning model on the learning activity of students in Christian Religious Education and Character Education in class X of SMA Negeri 1 Sipoholon in the 2024/2025 Academic Year: 1) Analysis requirements test: a) positive relationship test obtained rxy value = 0.548> rtable ( = 0.05, n = 41) = 0.308 thus it is known that there is a positive relationship between variable X and variable Y. b) Significant relationship test obtained tcount value = 4.089> ttable ( = 0.05, dk = n-2 = 39) = 2.021 thus there is a significant relationship between variable X and variable Y. 2) Influence test: a) Regression equation test, obtained regression equation Y ̂="42","64"+0.84X. b) Regression determination coefficient test (r2) = 30%. 3) Hypothesis testing using the F test obtained Fcount > Ftable = ( = 0.05, df numerator k = 15, df denominator = n-2 = 41-2 = 39) which is 16.70 > 1.92. Thus Ha, namely there is an influence of the Problem Solving learning model on the learning activity of students in Christian Religious Education and Character Education in class X of SMA Negeri 1 Sipoholon in the 2024/2025 Academic Year is accepted and H0 is rejected.